Best Evidence Summary of Home Enteral Tube Feeding Care Management in the Elderly - Zhu H; Liu A; Han Z; Yang Y; Ma X; Shi H (Patient Preference and Adherence)
Huiya Zhu,1 Aihua Liu,1 Zhongyan Han,2 Yanling Yang,3 Xiao Ma,2 Haiyan Shi2 1Department of Cardiovasology, the Second Medical Center & National Clinical Research Center for Geriatric Diseases, Chinese PLA General Hospital, Beijing, People’s Republic of China; 2Department of Gastroenterology, the Second Medical Center & National Clinical Research Center for Geriatric Diseases, Chinese PLA General Hospital, Beijing, People’s Republic of China; 3Department of Neurology, PLA Rocket Force Characteristic Medical Center, Beijing, People’s Republic of ChinaCorrespondence: Haiyan Shi, Department of Gastroenterology, the Second Medical Center & National Clinical Research Center for Geriatric Diseases, Chinese PLA General Hospital, Beijing, 100853, People’s Republic of China, Email shihyan662@163.comPurpose: To evaluate and summarize the best evidence of home enteral tube feeding (HETF) care management in the elderly to provide an evidence-based basis for caregivers to implement care interventions.Patients and Methods: Evidence on HETF care management in the elderly was retrieved from Chinese and international databases, guidelines, and websites of professional associations, including systematic reviews and expert consensuses, using the keywords of home enteral nutrition, home tube feeding, old, elder, home care, etc. The literature considered in this study was published from April 2019 to April 2024. Two trained researchers independently evaluated the quality of the included literature, graded the literature using the JBI evidence pre-grading system, classified and summarized the extracted evidence.Results: A total of 15 articles were included, including 1 clinical decision, 1 guideline, 3 best evidence summaries, 4 systematic reviews, 2 randomized controlled trials, and 4 quasi-experimental studies. 18 pieces of the best evidence were summarized in 3 aspects, including the NST administration, education of caregivers, and selection of nutrition formulas.Conclusion: This study comprehensively summarized the best evidence of home enteral tube feeding care management in the elderly and provided a scientific basis for caregivers to implement care interventions. In home care settings, using evidence-based practices requires developing a comprehensive care management system based on the trinity of hospital, community and home, in order to reduce the incidence of HETF-related complications, improve the quality of life of the elderly with HETF, and provide a practical reference for NST members and caregivers.Keywords: enteral nutrition, nutritional support, quality of life, complication prevention, patient education